2021
DOI: 10.1101/2021.11.26.470115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Survey on Open Science Practices in Functional Neuroimaging

Abstract: Replicability and reproducibility of scientific findings is paramount for sustainable progress in neuroscience. Preregistration of the hypotheses and methods of an empirical study before analysis, the sharing of primary research data, and compliance with data standards such as the Brain Imaging Data Structure (BIDS), are considered effective practices to secure progress and to substantiate quality of research. We investigated the current level of adoption of open science practices in neuroimaging and the diffi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
(53 reference statements)
1
4
0
Order By: Relevance
“…The percentage of collected data that is publicly shared remains therefore unclear but is certainly well below 45%. This result is consistent with a previous survey on open science practices in functional neuroimaging which reported that 34% of their participants have never shared their raw neuroimaging data (Paret et al, 2021). This similarity could also be caused by the fact that half of respondents in our survey are engaged in neuroimaging.…”
Section: Discussionsupporting
confidence: 92%
“…The percentage of collected data that is publicly shared remains therefore unclear but is certainly well below 45%. This result is consistent with a previous survey on open science practices in functional neuroimaging which reported that 34% of their participants have never shared their raw neuroimaging data (Paret et al, 2021). This similarity could also be caused by the fact that half of respondents in our survey are engaged in neuroimaging.…”
Section: Discussionsupporting
confidence: 92%
“…In a recent survey of neuroimaging researchers, 54% indicated that they were likely to share all raw imaging data in online repositories for their next project ( Paret et al, 2022). This demonstrates an impressive commitment from much of the neuroimaging community to transparent and accountable science.…”
Section: Reflect On What Needs To Be Sharedmentioning
confidence: 99%
“…Even when members of a specific scientific community have taken a central role in open science advocacy and tool development, like in the neuroimaging community, the impact on the rest of the very same community is limited. A recent survey (Paret et al 2021) including researchers who are senior and likely to hold a positive attitude towards open science, indicated that 42% have never pre-registered a neuroimaging study and 34% have never shared their raw neuroimaging data. Many of those who indicated that they pre-registered or shared their data at least once likely did not do so in all their studies, and thus, the actual rate of pre-registration and data sharing in neuroimaging is likely much lower.…”
Section: Empirical Observations Of How Labs Conduct Research Indicate...mentioning
confidence: 99%
“…Likewise, a more recent survey indicated that similar percentages of researchers in neuroimaging have never learned how to pre-register or share their data online and that they know too little about pre-registration platforms and suitable data repositories (Paret et al 2021). These later challenges could be alleviated by a simplified overview of the open resources available.…”
Section: Empirical Observations Of How Labs Conduct Research Indicate...mentioning
confidence: 99%